Pengaruh Promosi dan Inovasi Produk terhadap Keputusan Pembelian : Survei pada Konsumen Konveksi ANsport di Wilayah Tasikmalaya - Riza Reziana Ruhimat; Depy Muhamad Pauzy; Ari Arisman (CV. Ulil Albab Corp, 2022)
This study aims to determine the effect simultaneously and partially of promotion, product inovation on purchase decision ANSport in Tasikmalaya City. The method used in this research is method a survey. The research data were obtained by distributing questionnaires to 100 respondents. Data analysis in this study used multiple regression analysis using SPSS software. The results of this study indicate that the promotion and product inovation simultaneously have a significant effect on purchase decision. promotion partially significant effect on purchase decision. product inovation has a significant effect on purchase decision.